In vivo cross-linking of EpsG to EpsL suggests a role for EpsL as an ATPase-pseudopilin coupling protein in the Type II secretion system of Vibrio cholerae - Miranda D. Gray; Michael Bagdasarian; Wim G. J. Hol; Maria Sandkvist (2010)
The type II secretion system is a multi-protein complex that spans the cell envelope of Gram-negative bacteria and promotes the secretion of proteins, including several virulence factors. This system is homologous to the type IV pilus biogenesis machinery and contains five proteins, EpsG-K, termed the pseudopilins that are structurally homologous to the type IV pilins. The major pseudopilin EpsG has been proposed to form a pilus-like structure in an energy-dependent process that requires the ATPase, EpsE. A key remaining question is how the membrane-bound EpsG interacts with the cytoplasmic ATPase, and if this is a direct or indirect interaction. Previous studies have established an interaction between the bitopic inner membrane protein EpsL and EpsE; therefore, in this study we used in vivo cross-linking to test the hypothesis that EpsG interacts with EpsL. Our findings suggest that EpsL may function as a scaffold to link EpsG and EpsE and thereby transduce the energy generated by ATP hydrolysis to support secretion. The recent discovery of structural homology between EpsL and a protein in the type IV pilus system implies that this interaction may be conserved and represent an important functional interaction for both the type II secretion and type IV pilus systems.